Managing sales and inventory variances in a community pharmacy - Timoteo, Christian S. (Animo Repository, 2022)
This insider action research presents how a community retail pharmacy was able to address the challenges in its business operations. Overarching issues were identified such as variances in sales and inventory of the store. These issues affected the operations of the business which resulted in the limitation of its profit generation that prevented the business in achieving one of its operational goals. Since the business is new and is yet to create its standard operating procedures, the management invested in a point of sale (POS) system. The POS system was purchased because they knew that sales and inventory should be managed systematically as these are two of the important factors to be considered in running a business. However, after months of operations, they noticed that there are shortages and overages in the daily sales. This is also the same with the store inventory which had variances in the physical versus the system count. Through a detailed analysis of the issue which included generation of sales and inventory reports and collaboration of the team (pharmacists and a pharmacy aide), investigations were conducted, and action plans were created and implemented to reduce the variances in both sales and inventory. Through the two cycles of this action research, the team was able to improve the current processes of the business, enhance teamwork and openness of its members and had a better understanding on how to handle unexpected situations in a retail pharmacy setting in a systematic way. Each team member’s sense of responsibility and accountability have also improved backed by feedback and exchange of ideas in the creation of best practices that benefited both the stakeholders and the business.